Dogielophis, a replacement name for Dogielina Sobolev 1950 (Nematoda) non Bogdanowicz & Woloszynova 1949 (Foraminifera) - Doweld, Alexander B. (Zootaxa, 2016)
The generic name Dogielina was proposed by Sobolev (in Skrjabin & al. 1950: 68; for Physaloptera inexpectata Dogiel & Bychowsky 1939: 93, type species by original designation) for a parasitic nematode of the fishes from the western shores of the Caspian Sea (Sara Island) of the former USSR (now Azerbaijan: Sarı adası, Nərimanabad). However, this name is already preoccupied by a fossil Foraminifera Dogielina Bogdanowicz & Woloszynova (1949: 185), published earlier in the same year (see note on publication dates below), which is in active current use in palaeontology and even served as a basis for a specific geological Dogielina sarmatica biozone in the Upper Miocene stratigraphy of Eurasia (Krézsek & Filipescu 2005). Besides this earliest generic name, a later homonym is also known in Protista: Dogielina Raabe (1959: 448) [Infusoria].